PROBLEMATIKA PENGEMBANGAN KREATIVITAS PESERTA DIDIK DALAM PEMBELAJARAN MATEMATIKA BERDASARKAN PERSEPSI GURU - T. Wirnoto; N. Ratnaningsih (Universitas Pendidikan Ganesha, 2022)
This research is a qualitative descriptive study that aims to explore information from the teacher's perception of the problems of developing students' creativity in learning mathematics. The subjects in this study were four mathematics teachers at MAN 2 Tasikmalaya. Collecting data using questionnaires, data analysis used is data reduction, data presentation and conclusion drawing. The results showed that the problems of developing students' creativity in learning mathematics, namely: 1) limited learning time, 2) different abilities of children, 3) students did not understand the prerequisite material, 4) limited hand phones and student quotas, 5) participants students do not have a personal source book that is used as a guide for independent study, 6) teachers find it difficult to check the answers to various divergent questions, 7) teachers still have difficulty making questions with nuances of problem solving and investigation, 8) students have difficulty in answering questions that nuances of problem solving and investigation, 9) students' reasoning and mathematical abilities, 10) teachers have difficulty in preparing trial and error learning, 11) there are still students who do not pay attention to learning, 12) students are still not active in asking and answering .